Effect of the combined centre of gravity height on the ride comfort of suspended monorail train under crosswinds - Bao, Yulong; Zhai, Wanming; Cai, Chengbiao; Zhu, Shengyang; Li, Yongle (Vehicle system dynamics, 2023)
The combined centre of gravity (CCOG) height of a suspended monorail train may have a certain influence on the centrifugal forces acting on the train under crosswinds, and changes in centrifugal forces will further affect the dynamic interactions among the crosswind, the vehicle and the bridge subsystem. To investigate the effect of CCOG height on the dynamic behaviour of the train, this paper proposes an improved wind-vehicle-bridge coupling dynamics model considering the CCOG height for the suspended monorail system, in which the uneven passenger weight distribution is simulated with various vehicle parameters, and the aerodynamic wind forces acting on the running vehicles and bridge are simulated considering the effect of resultant wind yaw angle. The influences of passenger number, wind velocity, and vehicle speed on the dynamic behaviours of suspended monorail trains are also explored. The results indicate that the suspended monorail train has a certain self-balancing ability due to its unique structure type, which causes the lateral responses of the car body to attenuate with the increasing car weight. In addition, it is conservative to not consider the effect of CCOG height in the lateral ride comfort evaluation of the suspended monorail train subject to crosswinds.